ANALISIS YURIDIS ATAS TINDAKAN DISKRIMINATIF SEBAGAI PELANGGARAN HAM RINGAN BERDASARKAN UNDANG- UNDANG NO. 40 TAHUN 2008 TENTANG PENGHAPUSAN DISKRIMINASI RAS DAN ETNIS - Zainal Abidin Pakpahan; Suhaidi Suhaidi; Faisal Akbar Nasution; Jelly Leviza (Universitas Sumatera Utara, 2013)
ABSTRACTPractice to action discriminative as collision of light human right in law order have been arranged in section 28B sentence (2), section 28I sentence (2) Indonesian constitution 1945 post amendment, then section 1 number 1 of constitution No. 40/2008 about discrimination disposal, race and ethnical, then discrimination context as collision of human right have been assured in section 1 number 3 of constitution no 39 the year 1999 about human right, so that action diskriminative has ought to be punishable if it has done. hence to action discriminative can be given sanction of imprisonment at longest one (1) year or penalty fine maximum one hundred million rupiahs according to at section 15 and 16 of constitution No. 40 the year 2008 about discrimination disposal race and ethnical. Refers such a of action perpetrator discriminative instead seldom be punished and their case have never been brought to justice of human right as justice judging about collision human right. Action discriminative as collision of light HAM cannot be judged in HAM justice domain, caused existence of historical reason that is, in Statute Roma 1998 adopting existence of four badness numbers which can be judged in ICC among others, badness of genosida, crimes againt humanity, badness of war and badness of aggression however doesn't coronate to collision of light HAM like action discriminative as collision of light HAM as which included in DUHAM 1948. Reason of yuridis, according to section 4 constitution No. 26 the year 2000 about justice of human right expresslies state that collision of human right which can be judged in justice of human right is collision of heavy HAM that is badness of genosida and badness to humanity outside from the badness justice of HAM doesn't have authority to investigate breaks and judges it, then reason of basis yuridis as presentation of the forming of constitution justice of human right in judging is special for collision of weight HAM which can be judged in justice of human right but not to collision of light HAM.Keyword : analysis yuridis, action discriminative, and light collusion human right.